Determinants of Vietnam’s Exports to ASEAN Countries in the Context of the ASEAN Economic Community - Duc, Le Anh; Nhuong, Bui Huy; Linh, Ha Dieu; Ha, Hoang Thi Thu; Anh, Dang Tuan; Huong, Tran Lan; Van, Le Thi Anh (Journal of Social Economics Research, 2022)
The ASEAN region is emerging as a dynamically developing region, and trade between Vietnam and ASEAN countries has continuously improved over the years. This study investigates the determinants of Vietnam’s exports to ASEAN countries from 1997 to 2020. The paper also examines the differences in the directions of the impact in different groups of exported products. Using pooled OLS and panel data methods, the results demonstrate that Vietnam’s exports increased as its GDP per capita and importing countries’ GDP per capita increased. In contrast, transportation costs proxied by geographic distance were found to have a negative impact on Vietnam’s exports. The results assert the positive relationship between exports and real bilateral exchange rate. The ASEAN Trade in Goods Agreement (ATIGA) was found to have no statistically significant influence on Vietnam’s exports. These results are vital for trade policy formulation to promote Vietnam’s exports to ASEAN countries. Vietnam should promote trade with countries sharing a border to take advantage of transportation costs and reduce potential risks in goods movement. In addition, it is necessary to minimize the effects of fluctuations in the exchange rate in order to further promote Vietnam's exports in the future.